Raw material composition of positive electrode material, positive electrode material, preparation method thereof, electrode sheet and battery
Patent Information
- Application Number
- CN202610786445.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-27
Smart Images

Figure SMS_14 
Figure SMS_15 
Figure SMS_16
Abstract
Description
Technical Field
[0001] This invention relates to a raw material composition for a positive electrode material, a positive electrode material and its preparation method, an electrode sheet, and a battery. Background Technology
[0002] In the manufacturing process of lithium-ion batteries (LIBs) and other high-performance energy storage devices, the performance of cathode materials directly determines the battery's energy density, power density, cycle life, and safety. With the increasing demand for high-energy-density and long-life batteries, the microstructure control of cathode materials (such as particle size distribution, crystal orientation, and conductive network construction) has become one of the key factors in improving battery performance. Furthermore, in the cathode material preparation process, the selection and usage strategy of the carbon source are core technical parameters affecting the performance of the final product.
[0003] However, traditional carbon sources (such as sucrose, glucose, starch, potassium carbonate, ethylene oxide, etc.) face several technical challenges in practical applications, such as: (1) Uneven carbon distribution: In solid-phase reactions, carbon sources are often difficult to be evenly distributed on the surface of all precursor particles, resulting in local carbon content that is too high or too low.
[0004] (2) Residual impurities: Some carbon sources do not burn completely at high temperatures, which may leave oxides or other impurities, affecting the purity and electrochemical performance of the cathode material.
[0005] (3) Particle aggregation: Some carbon sources (such as starch) may cause aggregation between active particles at high temperatures, increasing the internal impedance of the electrode.
[0006] (4) Cost and safety: Some high-efficiency carbon sources (such as ethylene oxide) are expensive or have certain safety risks.
[0007] In summary, traditional carbon sources still have shortcomings. There is an urgent need for a novel carbon source for preparing cathode materials that can form a stable and uniform carbon coating layer during high-temperature calcination, thereby further improving the electrochemical performance of the batteries obtained from the cathode materials. Summary of the Invention
[0008] The technical problem this invention aims to solve is to overcome the shortcomings of existing technologies where insufficient carbon sources lead to poor electrochemical performance in batteries made from the resulting cathode materials. This invention provides a raw material composition for a cathode material, the cathode material itself, a method for preparing the same, an electrode sheet, and a battery. The cathode material prepared using the raw material composition of this application exhibits lower powder resistivity and better compaction density; the battery made from this cathode material demonstrates superior electrochemical performance.
[0009] The present invention solves the above-mentioned technical problems through the following technical solution: The present invention provides a raw material composition for a cathode material, comprising a carbon source; the carbon source comprises phenolic ether compounds; the phenolic ether compounds account for 42%-60% of the mass percentage of the carbon source.
[0010] In this invention, the phenolic ether compounds refer to compounds formed by replacing the hydrogen on the phenolic hydroxyl group with a group containing an ether bond.
[0011] In this invention, the phenolic ether compound preferably has the structure shown in Formula I: Formula I; R1 is -H, straight chain, or branched C. 1~10 One of the alkyl groups, for example -H; R2, R3, and R4 are each independently selected from -H, straight-chain, or branched C. 1~20 One of the alkyl groups, for example -H; the straight-chain C 1~20 The alkyl group is preferably a straight-chain C2 alkyl group; the branched C2 alkyl group is... 1~20 The alkyl group is preferably a branched C8 alkyl group; for example, CH3-C(CH3)2-CH2-C(CH3)2-. M1 is R 12 Selected from -H, -CH3 or -CH2CH3, for example -H; n=1-5000, preferably 5-30, for example 10, 15 or 20.
[0012] In this invention, the phenolic ether compound preferably has the structure shown in Formula II: Formula II; Among them, R5, R6, R7, R8, R9, R 10 At least one of them is -OM2R 11 The rest are -H or -OH; R 11 -H, straight chain or branched chain C 1~10 One of the alkyl groups; M2 is R 13 and R 14 Each is independently selected from -H, -CH3 or -CH2CH3, for example -H; n1=1-5000, preferably 5-30, for example 10, 12, 15 or 25; n2=1-5000, preferably 5-30, for example 8, 10, 12 or 15.
[0013] In a preferred embodiment 1, the phenolic ether compound has the structure shown in Formula I above, where R2, R3, and R4 are all -H; M1 is... R 12Selected from -H; n=10; R1 is -H.
[0014] In a preferred embodiment 2, the phenolic ether compound has the structure shown in Formula I above, where R2 and R3 are both -H; R4 is CH3-C(CH3)2-CH2-C(CH3)2-; and M1 is... R 12 Selected from -H; n=10; R1 is -H.
[0015] In a preferred embodiment 3, the phenolic ether compound has the structure shown in Formula I above, where R2 and R4 are both -H; R3 is... M1 is R 12 Selected from -H; n=20; R1 is -H.
[0016] In a preferred embodiment 4, the phenolic ether compound has the structure shown in Formula I above, where R2 and R3 are both -H; R4 is -C2H5; and M1 is... R 12 Selected from -H; n=15; R1 is -H.
[0017] In a preferred embodiment 5, the phenolic ether compound has the structure shown in Formula II above, R5, R6, R7, R9, R 10 -H; R8 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12, n2 is 0.
[0018] In a preferred embodiment 6, the phenolic ether compound has the structure shown in Formula II above, where R5, R6, R7, R8, and R9 are -H; R 10 -OM2R 11 M2 is R 13 Selected from -H; n1 is 15, n2 is 0.
[0019] In a preferred embodiment 7, the phenolic ether compound has the structure shown in Formula II above, R5, R7, R8, R9 and R 10 -H; R6 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12.5, R 14 Selected from -CH3, n2 is 4; R 11 Selected from -H; R8 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12.5, R 14Selected from -CH3, n2 is 4; R 11 Selected from -H.
[0020] In this invention, the phenolic ether compound accounts for 45%-60% of the mass percentage of the carbon source, for example, 50%, 52.6%, 53.8%, 45.5%, 57.1%, 55% or 60%.
[0021] In this invention, the carbon source accounts for 3%-20% of the mass percentage of the raw material composition of the cathode material, preferably 5%-15%, for example 8.9%, 9.5%, 8.2%, 10.2%, 6.5%, 6.8%, 7.1% or 12%.
[0022] In this invention, the carbon source may also include other carbon sources, preferably one or more selected from sucrose, glucose, polyethylene glycol, starch, citric acid, and asphalt, such as polyethylene glycol and / or glucose. The polyethylene glycol is preferably PEG1500, PEG6000, or PEG-200.
[0023] In a preferred embodiment, the carbon source includes glucose and the phenolic ether compound, and the mass ratio of glucose to the phenolic ether compound can be (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1.
[0024] In a preferred embodiment, the carbon source includes polyethylene glycol and the bisphenol compound, and the mass ratio of the polyethylene glycol to the phenolic ether compound can be (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1.
[0025] In a more preferred embodiment, the carbon source includes octylphenol polyoxyethylene (10) ether and glucose.
[0026] In a more preferred embodiment, the carbon source includes phenol polyoxyethylene (10) ether and glucose.
[0027] In a more preferred embodiment, the carbon source includes cashew phenol polyoxyethylene (20) ether and glucose.
[0028] In a more preferred embodiment, the carbon source includes p-ethylphenol polyoxyethylene (15) ether and glucose.
[0029] In a more preferred embodiment, the carbon source comprises 1-naphthol polyoxyethylene (12) ether and glucose.
[0030] In a more preferred embodiment, the carbon source comprises 2-naphthol polyoxyethylene (15) ether and glucose.
[0031] In a more preferred embodiment, the carbon source comprises 1,7-dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether and glucose.
[0032] In a more preferred embodiment, the carbon source includes octylphenol polyoxyethylene (10) ether and PEG200.
[0033] In this invention, the raw material composition of the positive electrode material also includes raw materials conventional in the art.
[0034] In this invention, the cathode material is preferably lithium iron phosphate, lithium manganese iron phosphate, or sodium iron manganese phosphate.
[0035] In a preferred embodiment, the cathode material is lithium iron phosphate, and the raw material composition of the cathode material includes an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent.
[0036] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example, 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example, 1.33:1 or 1:1. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130, 995:226:6.73:110, 995:226:6.73:140.
[0037] The raw material composition of the cathode material further includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.
[0038] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the raw material composition of the cathode material includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent.
[0039] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:90:1000, 350:1250:9:12:95:1000 or 350:1250:9:12:100:1000.
[0040] In a preferred embodiment, the positive electrode material is sodium iron manganese phosphate, and the raw material composition of the positive electrode material includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent.
[0041] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese, and phosphorus elements, the molar ratio of the sodium source, phosphorus source, iron source, and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. Based on carbon, iron, and manganese elements, the molar ratio of the carbon source to the iron and manganese sources is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.
[0042] The present invention provides a method for preparing a cathode material, comprising the following steps: sintering a precursor slurry to obtain the cathode material; wherein the precursor slurry comprises the raw material composition of the cathode material as described above.
[0043] In this invention, the sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8 or 12h.
[0044] In this invention, the sintering is preferably carried out under an inert atmosphere, such as a nitrogen atmosphere.
[0045] In this invention, the heating rate from room temperature to the sintering temperature is preferably 1-10°C / min, more preferably 2-6°C / min, for example 3 or 5°C / min.
[0046] In this invention, the sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.
[0047] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.
[0048] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.
[0049] In a preferred embodiment, the cathode material is lithium iron phosphate, and the preparation method of the cathode material includes the following steps: spray granulation and sintering of the precursor slurry; the precursor slurry includes an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent.
[0050] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example, 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example, 1.33:1 or 1:1. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130, 995:226:6.73:110, 995:226:6.73:140.
[0051] The solid content of the precursor slurry is preferably 30-60%, more preferably 35-50%, for example 40%. The D50 of the precursor slurry is preferably 250-500nm, more preferably 350-400nm, for example 370-380nm.
[0052] The precursor slurry is preferably obtained by mixing an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent, followed by sand milling. The sand milling time is preferably 60-180 min, more preferably 90-150 min, for example 120 min.
[0053] The precursor slurry preferably also includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.
[0054] The spray granulation temperature is preferably 180-300℃, more preferably 200-240℃, for example 220℃. During spray granulation, the flow rate of the precursor slurry is preferably 600-1000 ml / h, more preferably 700-900 ml / h, for example 800 ml / h.
[0055] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the preparation method of the cathode material includes the following steps: sintering a precursor slurry; the precursor slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent.
[0056] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:90:1000, 350:1250:9:12:95:1000 or 350:1250:9:12:100:1000.
[0057] The precursor slurry is preferably obtained by ball milling a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent. The ball milling speed is preferably 200-400 r / min, more preferably 250-300 r / min, for example, 280 r / min. The ball milling time is preferably 1-7 h, more preferably 3-5 h, for example, 4 h. The ball-to-material ratio during ball milling is preferably (4-12):1, more preferably (6-10):1, for example, 8:1.
[0058] Prior to sintering, the precursor slurry preferably undergoes a process of solvent removal and particle size control. The solvent removal method can be conventional in the art, such as vacuum drying. The vacuum drying temperature is preferably 40-70°C, more preferably 50-60°C, for example 55°C. The vacuum drying time is preferably 5-12 hours, more preferably 6-10 hours, for example 8 hours. The particle size control method can be conventional in the art, such as grinding. The endpoint of particle size control is preferably that the material can pass through a 100-mesh sieve.
[0059] The sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.
[0060] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.
[0061] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.
[0062] In a preferred embodiment, the cathode material is sodium iron manganese phosphate, and the preparation method of the cathode material includes the following steps: calcining a precursor slurry; the precursor slurry includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent.
[0063] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The carbon source includes glucose and phenolic ether compounds; or polyethylene glycol and phenolic ether compounds. The mass ratio of glucose to phenolic ether compounds can be (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1. The mass ratio of polyethylene glycol to phenolic ether compounds can be (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese, and phosphorus elements, the molar ratio of the sodium source, phosphorus source, iron source, and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. Based on carbon, iron, and manganese elements, the molar ratio of the carbon source to the iron and manganese sources is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.
[0064] The solid content of the precursor slurry is preferably 30-60 wt%, more preferably 45-55 wt%, for example 50 wt%.
[0065] The precursor slurry is preferably obtained by mixing a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent, followed by sand milling. The sand milling speed is preferably 1400-2600 r / min, more preferably 1800-2200 r / min, for example, 2000 r / min. The sand milling time is preferably 3-10 h, more preferably 5-7 h, for example, 6 h.
[0066] The sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h. The heating rate from room temperature to the sintering temperature is preferably 1-10℃ / min, more preferably 2-6℃ / min, for example 3 or 5℃ / min.
[0067] In this invention, phenolic ether compounds containing aromatic rings are selected as one of the carbon sources for preparing cathode materials. Because phenolic ether compounds contain aromatic rings in their molecular structure, the presence of aromatic ring structure significantly improves the residual carbon rate of the carbon source. Therefore, in the process of preparing cathode materials, the amount of carbon source added and the raw material cost of cathode materials can be significantly reduced. Moreover, as a rigid structure, the aromatic ring is easy to generate ordered graphitized coated carbon on the surface of cathode material particles, thereby improving the conductivity and charge / discharge capacity of the battery obtained from the cathode material.
[0068] This invention provides a cathode material, which is prepared using the cathode material preparation method described above.
[0069] The present invention provides an electrode sheet comprising the positive electrode material as described above.
[0070] The present invention provides a battery comprising the electrodes as described above.
[0071] The positive and progressive effects of this invention are as follows: The positive and progressive effects of this invention are as follows: The cathode material prepared using the raw material composition of the cathode material of this application has a lower powder resistivity and a better compaction density; the battery made from the cathode material has better electrochemical performance. Detailed Implementation
[0072] The present invention will be further illustrated by way of embodiments below, but the present invention is not limited to the scope of the embodiments described herein.
[0073] The structural formulas of the phenolic ether compounds used in the following examples or comparative examples are as follows: 1. Phenolic polyoxyethylene (10) ether
[0074] 2. Octylphenol polyoxyethylene (10) ether
[0075] 3. Cashew phenol polyoxyethylene (20) ether
[0076] 4. p-Ethylphenol polyoxyethylene (15) ether
[0077] 5. 1-Naphthol polyoxyethylene (12) ether
[0078] 6. 2-Naphthol polyoxyethylene (15) ether
[0079] 7. 1,7-Dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether
[0080] I. Preparation of Lithium Iron Phosphate Materials
[0081] Example 1
[0082] The raw material composition of the cathode material includes: octylphenol polyoxyethylene (10) ether and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant. The carbon source accounts for 8.9% by mass in the raw material composition of the cathode material, and phenolic ether compounds account for 50% by mass of the carbon source. 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 60 parts of octylphenol polyoxyethylene (10) ether were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mill was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate cathode material.
[0083] The obtained lithium iron phosphate cathode material was crushed to powder with a particle size D50 of 1.2-1.3μm using a traditional Chinese medicine crusher (Teruisi traditional Chinese medicine pulverizer); the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.
[0084] Example 2
[0085] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with phenol polyoxyethylene (10) ether, and the amount added is 70 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 9.5%; and the mass percentage of phenolic ether compounds in the carbon source is 53.8%.
[0086] Example 3
[0087] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with cashew phenol polyoxyethylene (20) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.2%; and the mass percentage of phenolic ether compounds in the carbon source is 45.5%.
[0088] Example 4
[0089] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with p-ethylphenol polyoxyethylene (15) ether, and the amount added is 80 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 10.2%; and the mass percentage of phenolic ether compounds in the carbon source is 57.1%.
[0090] Example 5
[0091] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with 1-naphthol polyoxyethylene (12) ether, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0092] Example 6
[0093] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with 2-naphthol polyoxyethylene (15) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.2%; and the mass percentage of phenolic ether compounds in the carbon source is 45.5%.
[0094] Example 7
[0095] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with 1,7-dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether, and the amount added is 70 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 9.5%; and the mass percentage of phenolic ether compounds in the carbon source is 53.8%.
[0096] Example 8
[0097] The only difference from Example 1 is that 60 parts of glucose are replaced with 60 parts of PEG200; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0098] Comparative Example 1
[0099] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0100] Comparative Example 2
[0101] The only difference from Example 1 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0102] Comparative Example 3
[0103] The only difference from Example 1 is that only 60 parts of glucose are added, and no phenolic ether carbon source is added; the mass percentage of carbon source in the raw material composition of the cathode material is 4.6%; and the mass percentage of phenolic ether compounds in the carbon source is 0%.
[0104] Comparative Example 4
[0105] The only difference from Example 2 is that only 70 parts of phenol polyoxyethylene (10) ether are added as a carbon source, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 5.4%; and the mass percentage of phenolic ether compounds in the carbon source is 100%.
[0106] Comparative Example 5
[0107] The only difference from Example 1 is that: the amount of octylphenol polyoxyethylene (10) ether added is 20 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.1%; and the mass percentage of phenolic ether compounds in the carbon source is 25%.
[0108] Comparative Example 6
[0109] The only difference from Example 1 is that: the amount of octylphenol polyoxyethylene (10) ether added is 100 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 11.5%; and the mass percentage of phenolic ether compounds in the carbon source is 62.5%.
[0110] II. Preparation of Lithium Manganese Iron Phosphate Materials
[0111] Example 9
[0112] The raw material composition of the cathode material includes: octylphenol polyoxyethylene (10) ether and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; amine ether compounds account for 50% of the mass percentage of carbon source. 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 45 parts glucose, 45 parts octylphenol polyoxyethylene (10) ether, 12 parts phosphoric acid and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain precursor slurry. The precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate cathode material.
[0113] Example 10
[0114] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with phenol polyoxyethylene (10) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.8%; and the mass percentage of phenolic ether compounds in the carbon source is 52.6%.
[0115] Example 11
[0116] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with cashew phenol polyoxyethylene (20) ether, and the amount added is 45 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0117] Example 12
[0118] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with p-ethylphenol polyoxyethylene (15) ether, and the amount added is 55 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 7.1%; and the mass percentage of phenolic ether compounds in the carbon source is 55%.
[0119] Example 13
[0120] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with 1-naphthol polyoxyethylene (12) ether, and the amount added is 50 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.8%; and the mass percentage of phenolic ether compounds in the carbon source is 52.6%.
[0121] Example 14
[0122] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with 2-naphthol polyoxyethylene (15) ether, and the amount added is 45 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0123] Example 15
[0124] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with 1,7-dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether, and the amount added is 55 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0125] Example 16
[0126] The only difference from Example 9 is that 45 parts of glucose are replaced with 45 parts of PEG200; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0127] Comparative Example 7
[0128] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500, and the amount added is 45 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0129] Comparative Example 8
[0130] The only difference from Example 9 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000, and the amount added is 45 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 6.5%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0131] Comparative Example 9
[0132] The only difference from Example 9 is that only 45 parts of glucose are added, and no phenolic ether compounds are added; the mass percentage of carbon source in the raw material composition of the cathode material is 3.3%; and the mass percentage of phenolic ether compounds in the carbon source is 0%.
[0133] Comparative Example 10
[0134] The only difference from Example 10 is that only 45 parts of phenol polyoxyethylene (10) ether are added as a carbon source, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 3.3%; and the mass percentage of phenolic ether compounds in the carbon source is 100%.
[0135] Comparative Example 11
[0136] The only difference from Example 9 is that: the amount of octylphenol polyoxyethylene (10) ether added is 10 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 4.1%; and the mass percentage of phenolic ether compounds in the carbon source is 18.2%.
[0137] Comparative Example 12
[0138] The only difference from Example 9 is that: the amount of octylphenol polyoxyethylene (10) ether added is 80 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.8%; and the mass percentage of phenolic ether compounds in the carbon source is 64%.
[0139] III. Preparation of Sodium Iron Manganese Phosphate Cathode Material for Sodium-Ion Batteries
[0140] Example 17
[0141] The raw material composition of the cathode material includes: octylphenol polyoxyethylene (10) ether and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide and manganese dioxide as sodium source, phosphorus source, iron source and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; phenolic ether compounds account for 50% of the mass percentage of carbon source; Glucose and octylphenol polyoxyethylene (10) ether were mixed in a mass ratio of 1:1 as a carbon source. The molar ratio of sodium, iron, manganese and phosphorus in the raw materials was controlled to be 4:2.98:0.01:4, and the molar ratio of the carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw material composition of the cathode material and water were put into a sand mill and ground at a speed of 2000 r / min for 6 h to obtain a precursor slurry with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere and then naturally cooled to obtain sodium iron manganese sodium phosphate cathode material for sodium-ion batteries.
[0142] Example 18
[0143] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with phenol polyoxyethylene (10) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0144] Example 19
[0145] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with cashew phenol polyoxyethylene (20) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0146] Example 20
[0147] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with p-ethylphenol polyoxyethylene (15) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0148] Example 21
[0149] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with 1-naphthol polyoxyethylene (12) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0150] Example 22
[0151] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with 2-naphthol polyoxyethylene (15) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0152] Example 23
[0153] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with 1,7-dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0154] Example 24
[0155] The only difference from Example 19 is that glucose is replaced with PEG200; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0156] Comparative Example 13
[0157] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG1500; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0158] Comparative Example 14
[0159] The only difference from Example 17 is that octylphenol polyoxyethylene (10) ether is replaced with polyethylene glycol PEG6000; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 50%.
[0160] Comparative Example 15
[0161] The only difference from Example 17 is that only glucose is added, and no phenolic ether compounds are added; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 0%.
[0162] Comparative Example 16
[0163] The only difference from Example 17 is that only phenol polyoxyethylene (10) ether is added as a carbon source, and glucose is not added; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of phenolic ether compounds in the carbon source is 100%.
[0164] Example 1
[0165] 1. The residual carbon content of the lithium iron phosphate cathode materials prepared in the examples and comparative examples was tested using a Shanghai Dekai HCS-140 high-frequency infrared carbon-sulfur analyzer.
[0166] 2. The powder resistivity and compaction density of the lithium iron phosphate cathode materials prepared in the examples and comparative examples were tested using the Xiamen Yuaneng four-probe powder resistivity PRCD2110.
[0167] The test results are shown in Table 1.
[0168] 3. The powder conductivity of the lithium manganese iron phosphate cathode material prepared in the examples and comparative examples was tested using the Xiamen Yuaneng four-probe powder resistivity PRCD2110.
[0169] The test results are shown in Table 2.
[0170] Example 2
[0171] 1. Batteries prepared using lithium iron phosphate as the positive electrode active material
[0172] The crushed lithium iron phosphate cathode material (LiFePO4) obtained in the above examples and comparative examples was mixed with the above raw materials in a mass ratio of LiFePO4:conductive carbon black:polyvinylidene fluoride (PVDF) = 8:1:1. N-methylpyrrolidone was added to prepare a cathode slurry with a solid content of 55%. This slurry was uniformly coated onto carbon-coated aluminum foil, vacuum dried, rolled, and punched into a 2.01 cm² area. 2 Electrode assembly. The negative electrode uses a lithium metal sheet, the separator uses Celgard 2400PE film, and the electrolyte uses a commercially available product (SS-SHRG004, Dongguan Shanshan Battery Materials Co., Ltd.). The positive electrode, separator, and negative electrode are assembled in one go in a glove box (high-purity Ar atmosphere), and then the electrolyte (1 mol / L NaClO4 + EC:DMC:EMC(1:1:1) + 5% FEC) is injected to obtain a coin cell.
[0173] The coin cell was subjected to constant current charge-discharge cycle test at 25℃ and 0.1C, with a charge-discharge voltage of 2.0-3.7V. The initial coulombic efficiency was calculated. There was no special test method. The initial coulombic efficiency = initial discharge specific capacity / initial charge specific capacity. The coin cell battery was tested for rate capability at 25℃ and 2C. The test results are shown in Table 1.
[0174] Table 1
[0175] As can be seen from the test results in Table 1, compared with the lithium iron phosphate cathode material prepared by using phenolic ether compounds as a carbon source in Examples 1-8, the lithium iron phosphate cathode material prepared by using phenolic ether compounds as a carbon source in Examples 1-8, under the same residual carbon content, has significantly lower powder resistivity, higher compaction density, and significantly improved first discharge capacity, first coulombic efficiency, and 2C rate performance of the prepared battery. This indicates that the lithium iron phosphate cathode material prepared by using phenolic ether compounds as one of the carbon sources in Examples 1-8 has excellent coin cell performance.
[0176] Comparing Examples 1, 4, 5, and 6, it is evident that there is a suitable range for the amount of carbon source and phenolic ether compound added. Both excessively high and low additions of carbon source and phenolic ether compound lead to a decrease in residual carbon content, resulting in a significant decline in the electrochemical performance of the resulting battery. When the amount of carbon source added is too low, the resulting lithium iron phosphate cathode material cannot construct a complete and stable conductive and bonding network, leading to a significant decrease in the electrochemical performance of the resulting battery. When the amount of carbon source added is too high, the carbon layer of the resulting lithium iron phosphate cathode material is too thick, which conversely lengthens the electron transport path between the active material particles and the carbon layer, increases the interfacial resistance, and also leads to a significant decrease in the electrochemical performance of the resulting battery.
[0177] Comparing Comparative Examples 1-2 and Examples 1-8, it is evident that, with the same total carbon source amount, the lithium iron phosphate cathode material prepared using phenolic ether compounds as one of the carbon sources has a significant advantage over the lithium iron phosphate cathode material prepared using PEG compounds as one of the carbon sources. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium iron phosphate cathode material. The aromatic ring structure in the phenolic ether compounds in Examples 1-8 can significantly improve the residual carbon rate of the carbon source, and the rigid structure of the aromatic ring is more conducive to the formation of ordered graphitized coated carbon. Therefore, the lithium iron phosphate cathode material prepared using this material has a significant advantage over Comparative Examples 1-2.
[0178] Compared with Example 1, Comparative Example 3 did not contain any amine phenol ether compounds, and lacked the aromatic ring structure that plays a special role in phenol ether compounds; thus affecting the first discharge capacity and first coulombic efficiency of the resulting coin cell.
[0179] Comparing Examples 1 and 8, it is evident that glucose and phenolic ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and phenolic ether compounds. Phenolic ether compounds, due to their unique aromatic ring structure, form ordered graphitized coated carbon, while glucose fills and forms a dense carbon layer. The absence of either leads to a significant increase in resistivity, affecting the initial discharge capacity and initial coulombic efficiency of the resulting coin cell. Furthermore, after the phenolic ether compounds adsorb to form ordered graphitized coated carbon, the large steric hindrance of PEG prevents it from effectively filling the spaces between the phenolic ether compounds, resulting in a certain degree of decrease in the compaction density of the resulting lithium iron phosphate cathode material and a certain degree of decrease in the electrical performance of the resulting coin cell.
[0180] 2. Batteries prepared using lithium manganese iron phosphate as the positive electrode active material
[0181] 85g of lithium manganese iron phosphate cathode material, 5g of polyvinylidene fluoride, 10g of conductive carbon black, and 150mL of N-methylpyrrolidone prepared in the above examples and comparative examples were placed in a beaker and mechanically stirred at 500r / min for 4h to form a slurry. The slurry was coated onto aluminum foil with a single-sided thickness of 80μm using a doctor blade coater. The foil was pre-dried in a 60℃ forced-air drying oven for 30min and then transferred to a 120℃ vacuum drying oven for 12h. The dried electrode was compacted using a roller press with a pressure controlled at 110MPa and cut into electrode sheets with a diameter of 14mm to obtain the cathode. Using lithium foil as the negative electrode and a Celgard 2400 polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 (EC:DEC = 1:1, v / v) as the electrolyte, the positive electrode, negative electrode, separator, and electrolyte were assembled in an argon glove box with water and oxygen content all below 1 ppm. After assembly, the cells were allowed to stand for 24 hours to obtain coin cells. The discharge specific capacity at 0.1C and 5C rates was tested under charge / discharge cutoff voltages of 3.0-4.3V; the capacity retention rate after 100 cycles at 5C charge / discharge rate was also tested. The results are shown in Table 2.
[0182] Table 2
[0183] As can be seen from the test results in Table 2, compared with the lithium iron phosphate cathode material prepared using phenolic ether compounds as a carbon source in Examples 9-16, the powder conductivity of the lithium iron phosphate cathode material prepared using phenolic ether compounds as a carbon source is significantly improved under the same residual carbon content. The initial discharge capacity and 5C capacity retention of the prepared coin cells are also significantly improved. This indicates that the lithium iron phosphate cathode material prepared using phenolic ether compounds as a carbon source in Examples 9-16 has excellent electrochemical performance.
[0184] Comparing Examples 9, 10, 11, and 12, it is shown that there is a suitable range for the amount of carbon source and phenolic ether compound added. Too high or too low an amount of carbon source and phenolic ether compound added will lead to a significant decrease in the electrochemical performance of the resulting battery.
[0185] Comparing Comparative Examples 7-8 and Examples 9-16, it is evident that, with the same total amount of carbon source, the lithium manganese iron phosphate cathode material prepared using phenolic ether compounds as a carbon source has a significant advantage over the lithium manganese iron phosphate cathode material prepared using PEG compounds as a carbon source. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium manganese iron phosphate cathode material. The aromatic ring structure in the phenolic ether compounds of Examples 9-16 facilitates uniform carbon source coating and can form cyclic structures during the pyrolysis process, thereby improving the degree of orderliness of the coated carbon. The lithium manganese iron phosphate cathode material prepared using these compounds exhibits a significant advantage over Comparative Examples 7-8.
[0186] Compared with Example 9, Comparative Example 9 did not contain any phenolic ether compounds, and lacked the aromatic ring structure that plays a special role in phenolic ether compounds; thus affecting the discharge specific capacity and capacity retention of the obtained coin cell.
[0187] Comparing Examples 9 and 16, it is evident that glucose and phenolic ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and phenolic ether compounds. The aromatic ring structure in the phenolic ether compounds can form a highly ordered graphitized carbon layer, while glucose fills and forms a dense carbon layer. The absence of either one leads to a significant decrease in powder conductivity, affecting the discharge specific capacity and capacity retention of the resulting coin cell. Furthermore, after the phenolic ether compounds adsorb and form a highly ordered graphitized carbon layer, the large steric hindrance of PEG prevents it from effectively filling the spaces between the phenolic ether compounds, resulting in a certain degree of decrease in the conductivity of the obtained lithium manganese iron phosphate cathode material powder and a certain degree of decrease in the electrical performance of the resulting coin cell.
[0188] 3. Batteries prepared using sodium iron manganese phosphate (sodium iron manganese phosphate) as the positive electrode active material for sodium-ion batteries.
[0189] The sodium-ion batteries prepared in the above examples and comparative examples were uniformly mixed with sodium iron manganese phosphate positive electrode material, acetylene black, and PVDF binder, and then coated onto aluminum foil. After vacuum baking at 100°C for 4 hours, electrode sheets were obtained. Based on the total weight of the positive electrode material, acetylene black, and PVDF binder, the amount of positive electrode material was 80 wt%, the amount of acetylene black was 10 wt%, and the amount of PVDF binder was 10 wt%. Using the sodium sheet as the negative electrode, a glass fiber optic GF / A Whatman potassium sodium lithium battery filter membrane was used as the separator, and a 0.8 M NaPF6 / EC-DMC electrolyte was used. Button batteries were assembled and their charge-discharge characteristics were tested. The charge-discharge current was 0.1C, where 1C = 129 mA / g. The discharge specific capacity and average discharge voltage of the comparative and examples are shown in Table 3.
[0190] Table 3
[0191] As can be seen from the test results in Table 3, compared with the sodium iron manganese phosphate cathode material prepared using phenolic ether compounds as a carbon source in Examples 17-24, the coin cells prepared using the sodium iron manganese phosphate cathode material prepared using phenolic ether compounds as a carbon source in Examples 17-24 show significantly improved discharge specific capacity and capacity retention rate. This indicates that the sodium iron manganese phosphate cathode material prepared using phenolic ether compounds as a carbon source in Examples 17-24 has excellent electrochemical performance.
[0192] Comparing Example 17 with Comparative Example 16 shows that there is a suitable range for the amount of carbon source and phenolic ether compound added. Too high or too low an amount of carbon source and phenolic ether compound added will lead to a significant decrease in the electrochemical performance of the resulting battery.
[0193] Comparing Comparative Examples 13-14 and Examples 17-24, it is evident that, with the same total amount of carbon source, the sodium iron manganese phosphate cathode material prepared using phenolic ether compounds as a carbon source has a significant advantage over the sodium iron manganese phosphate cathode material prepared using PEG compounds as a carbon source. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared sodium iron manganese phosphate cathode material. The aromatic ring structure in the phenolic ether compounds of Examples 17-27 facilitates uniform coating of the carbon source and can form cyclic structures during the pyrolysis process, thereby improving the degree of orderliness of the coated carbon. The sodium iron manganese phosphate cathode material prepared using these compounds exhibits a significant advantage over Comparative Examples 13-14.
[0194] Compared with Example 17, Comparative Example 15 did not contain any phenolic ether compounds, and lacked the aromatic ring structure that plays a special role in phenolic ether compounds; thus affecting the discharge specific capacity and capacity retention of the resulting coin cell.
[0195] Comparing Examples 24 and 17, it is evident that glucose and phenolic ether compounds exhibit a stronger synergistic effect as a combined carbon source compared to the combination of PEG and phenolic ether compounds. The aromatic ring structure in the phenolic ether compounds can form a highly ordered graphitized carbon layer, while glucose fills and forms a dense carbon layer. The absence of either one leads to a significant decrease in powder conductivity, affecting the discharge specific capacity and capacity retention of the resulting coin cell. Furthermore, after the phenolic ether compounds adsorb and form a highly ordered graphitized carbon layer, the large steric hindrance of PEG prevents it from effectively filling the spaces between the phenolic ether compounds, resulting in a certain degree of decrease in the conductivity of the obtained sodium iron manganese phosphate cathode material powder and a certain degree of decrease in the electrical performance of the resulting coin cell.
[0196] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A raw material composition for a positive electrode material, characterized in that, It includes a carbon source; the carbon source includes phenolic ether compounds; the phenolic ether compounds account for 42%-60% of the mass percentage of the carbon source.
2. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The phenolic ether compound has the structure shown in Formula I: Equation I; Where R1 is -H, straight chain or branched chain C 1~10 One of the alkyl groups, for example -H; Among them, R2, R3, and R4 are each independently selected from -H, straight chain, or branched chain C. 1~20 One of the alkyl groups, for example -H; the straight-chain C 1~20 The alkyl group is preferably a straight-chain C2 alkyl group; the branched C2 alkyl group is... 1~20 The alkyl group is preferably a branched C8 alkyl group; for example, CH3-C(CH3)2-CH2-C(CH3)2-. Where M1 is R 12 Selected from -H, -CH3 or -CH2CH3, for example -H; n=1-5000, preferably 5-30, for example 10, 15 or 20; (2) The phenolic ether compound preferably has the structure shown in Formula II: Formula II; Among them, R5, R6, R7, R8, R9, R 10 At least one of them is -OM2R 11 The rest are -H or -OH; R 11 -H, straight chain or branched chain C 1~10 One of the alkyl groups; M2 is R 13 and R 14 Each is independently selected from -H, -CH3 or -CH2CH3, for example -H; n1=1-5000, preferably 5-30, for example 10, 12, 15 or 25; n2=1-5000, preferably 5-30, for example 8, 10, 12 or 15.
3. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the cathode material satisfies any one of the following conditions: The phenolic ether compound has the structure shown in Formula I as described in claim 2, wherein R2, R3, and R4 are all -H; M1 is... R 12 Selected from -H; n=10; R1 is -H; Alternatively, the phenolic ether compound has the structure shown in Formula I as described in claim 2, wherein R2 and R3 are both -H; R4 is CH3-C(CH3)2-CH2-C(CH3)2-; and M1 is... R 12 Selected from -H; n=10; R1 is -H; Alternatively, the phenolic ether compound has the structure shown in Formula I as described in claim 2, where R2 and R4 are both -H; R3 is... M1 is R 12 Selected from -H; n=20; R1 is -H; Alternatively, the phenolic ether compound has the structure shown in Formula I as described in claim 2, wherein R2 and R3 are both -H; R4 is -C2H5; and M1 is... R 12 Selected from -H; n=15; R1 is -H; Alternatively, the phenolic ether compound has the structure shown in Formula II as described in claim 2, wherein R5, R6, R7, R9, R 10 -H; R8 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12, n2 is 0; Alternatively, the phenolic ether compound has the structure shown in Formula II as described in claim 2, wherein R5, R6, R7, R8, and R9 are -H; R 10 -OM2R 11 M2 is R 13 Selected from -H; n1 is 15, n2 is 0; Alternatively, the phenolic ether compound has the structure shown in Formula II as described in claim 2, wherein R5, R7, R8, R9, and R 10 -H; R6 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12.5, R 14 Selected from -CH3, n2 is 4; R 11 Selected from -H; R8 is -OM2R 11 M2 is R 13 Selected from -H; n1 is 12.5, R 14 Selected from -CH3, n2 is 4; R 11 Selected from -H.
4. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The phenolic ether compound accounts for 45%-60% of the mass of the carbon source, for example, 50%, 52.6%, 53.8%, 45.5%, 57.1%, 55% or 60%; (2) The carbon source accounts for 3%-20% of the mass percentage of the raw material composition of the cathode material, preferably 5%-15%, for example 8.9%, 9.5%, 8.2%, 10.2%, 6.5%, 6.8%, 7.1% or 12%.
5. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the positive electrode material satisfies (1) and / or (2) of the following conditions: (1) The carbon source also includes one or more of sucrose, glucose, polyethylene glycol, starch, citric acid and asphalt, such as polyethylene glycol and / or glucose; the polyethylene glycol is preferably PEG1500, PEG6000 or PEG-200; The carbon source includes glucose and the phenolic ether compound, and the mass ratio of glucose to the phenolic ether compound is preferably (0.3-8):1, preferably (0.5-5):1, for example 1:1, 0.85:1, 1.2:1, 0.82:1, 0.75:1 or 0.9:1; The carbon source includes polyethylene glycol and the bisphenol compound, and the mass ratio of polyethylene glycol to the phenolic ether compound is preferably (0.5-2:1), preferably (0.8-1.5):1, for example 1.33:1 or 1:1; More preferably, the carbon source satisfies any one of the following conditions: ①The carbon source includes octylphenol polyoxyethylene (10) ether and glucose; ②The carbon source includes phenol polyoxyethylene (10) ether and glucose; ③The carbon source includes cashew phenol polyoxyethylene (20) ether and glucose; ④ The carbon source includes p-ethylphenol polyoxyethylene (15) ether and glucose; ⑤ The carbon source includes 1-naphthol polyoxyethylene (12) ether and glucose; ⑥ The carbon source includes 2-naphthol polyoxyethylene (15) ether and glucose; ⑦ The carbon source includes 1,7-dihydroxynaphthalene polyoxyethylene (25) ether polyoxypropylene (8) ether and glucose; ⑧ The carbon source includes octylphenol polyoxyethylene (10) ether and PEG200; (2) The positive electrode material is lithium iron phosphate, lithium manganese iron phosphate or sodium iron manganese phosphate.
6. A method for preparing a positive electrode material, characterized in that, It includes the following steps: sintering the precursor slurry to obtain the cathode material; the precursor slurry includes the raw material composition of the cathode material as described in any one of claims 1-5.
7. The method for preparing the cathode material as described in claim 6, characterized in that, The method for preparing the cathode material satisfies one or more of the following conditions: (1) The sintering temperature is 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃; (2) The sintering time is 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h; (3) The heating rate from room temperature to the sintering temperature is 1-10℃ / min, preferably 2-6℃ / min, for example 3 or 5℃ / min; (4) The sintering is divided into a first-stage sintering and a second-stage sintering, and the temperature of the second-stage sintering is higher than that of the first-stage sintering; The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃; the sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h; the heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min; The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃; the preferred sintering time for the second stage is 5-10h, more preferably 7-9h, for example 8h; and the preferred heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.
8. A positive electrode material, characterized in that, It is prepared using the method for preparing the positive electrode material as described in claim 6 or 7.
9. An electrode sheet, characterized in that, It includes the cathode material as described in claim 8.
10. A battery, characterized in that, It includes the electrode as described in claim 9.